Exercise and taurine in inflammation, cognition, and peripheral markers of blood-brain barrier integrity in older women - Matheus Uba Chupel; Luciele G. Minuzzi; Guilherme Eustaquio Furtado; Mario L. Santos; Eef Hogervorst; Edith Filaire; Ana Maria Teixeira (2018)
Immunosenescence contribute to increase the blood-brain barrier (BBB) permeability, leading cognitive impairment and neurodegeneration. Thus, we investigated the anti-inflammatory effect of exercise and taurine supplementation on peripheral markers of blood-brain barrier, inflammation, and cognition of elderly women. Forty-eight elderly women (83.58±6.9 years) participated in the study, and were allocated into combined exercise training (CET: n=13), taurine supplementation (TAU: n=12), exercise training associated with taurine (CET+TAU: n=11), or control group (CG: n=12). Exercise was applied twice a week (multi-modal exercise). Taurine ingestion was 1.5g., once a day. Participants were evaluated before and after 14-weeks of intervention. Plasma levels of IL-1β, IL-1ra, IL-6, IL-10, IL-17, TNF-α, and serum concentration of S100β and neuron specific enolase (NSE) were determined. The mini mental state examination (MMSE) was also applied. Concentrations of S100β were maintained in all intervention groups, while a subtle increase in the CG was found. NSE levels increased only in TAU group (p